TREATMENT OF THE CHILD WITH A MEDICAL EMERGENCY - Ana Vrankar; Maja Primec; Nada Fujs; Kaja Podlogar; Janja Skubic; Boštjan Tomelj; Judita Kolenc; Ana Gianini; Anita Štih (The Society for Children with Metabolic Disorders, 2021)
Emergency conditions in a child manifest themselves as a failure of one or more vital functions and would, without emergency intervention, lead to severe impairment or dis-ability in the child or even death. A very important task of the nurse is to identify the child's life-threatening condition and to act quickly and appropriately. Since 2010, the Department of Emergency Paediatrics has been operating at the Children's Hospital, University Medical Centre Ljubljana. It acts as a 24-hour admission centre for the Hospital. A child who comes to the emergency room without a referral or with a referral from a doctor in another speciality, reports to the admission clinic, where triage takes place. Triage, which is performed by nurses with special knowledge, is based on the principles of the Manchester Triage System in Emergency Paediatrics. There are many emergencies in paediatrics. This paper presents the most common life-threatening conditions such as status epilepticus, acute respiratory distress, paroxysmal supraventricular tachycardia and diabetic ketoacidosis. The role of the nurse in treating a child with an emergency condition, the scales for pain assessment and the role of the nurse in the treatment of the child with pain, are presented. Dealing with emergencies is a major challenge for every medical team. It requires nurses to undergo continuing education and to renew acquired skills.